2016
DOI: 10.1002/2015gc006232
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the northern Argentine margin during the Cenozoic controlled by bottom current dynamics and gravitational processes

Abstract: A detailed reflection seismic investigation on sediment deposition at the northern Argentine margin (37°S to 42°S) resolves major modifications in oceanographic circulation during the Cenozoic, which resulted from variations in both climatic and tectonic processes. After an extensive erosional period following the onset of glaciation of Antartica at ~34 Ma, which affected all water depth levels, a buried elongated mounded drift within the continental shelf was shaped by bottom current activity during the Mioce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 76 publications
1
17
0
1
Order By: Relevance
“…The Miocene synorogenic units are covered by a thin carpet of piedmont and glaciofluvial gravel deposits and by widespread basaltic lava flows. In contrast, the upper Miocene—lower Pliocene constitutes an aggradational period that is particularly well developed in the Argentine continental margin (Figure 14; Ercilla et al., 2019; Ghiglione et al., 2016; Gruetzner et al., 2016). The sediment eroded from the interior of the range likely bypassed Patagonia and reached the offshore basins, where they are represented by thick sequences with high sedimentation rates (Gruetzner et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Miocene synorogenic units are covered by a thin carpet of piedmont and glaciofluvial gravel deposits and by widespread basaltic lava flows. In contrast, the upper Miocene—lower Pliocene constitutes an aggradational period that is particularly well developed in the Argentine continental margin (Figure 14; Ercilla et al., 2019; Ghiglione et al., 2016; Gruetzner et al., 2016). The sediment eroded from the interior of the range likely bypassed Patagonia and reached the offshore basins, where they are represented by thick sequences with high sedimentation rates (Gruetzner et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the upper Miocene—lower Pliocene constitutes an aggradational period that is particularly well developed in the Argentine continental margin (Figure 14; Ercilla et al., 2019; Ghiglione et al., 2016; Gruetzner et al., 2016). The sediment eroded from the interior of the range likely bypassed Patagonia and reached the offshore basins, where they are represented by thick sequences with high sedimentation rates (Gruetzner et al., 2016). This regional reorganization of the sediment routing pattern includes evidence of diminished foreland subsidence and can be interpreted as the result of progressive foreland abandonment and sediment bypass during reduced activity on thrust faults (Figure 15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drifts are also present farther north along the margin (e.g., Hernández-Molina et al, 2015) with drifts apparently associated with flows of Antarctic Intermediate Water (AAIW), Upper Circumpolar Deep Water (UCDW), North Atlantic Deep Water (NADW), Lower Circumpolar Deep Water (LCDW) and Antarctic Bottom Water (AABW). Violante et al (2010) and Grützner et al (2011Grützner et al ( , 2012Grützner et al ( , 2016 suggested that increased sediment flux to the margin during the Miocene may in part be related to an uplift in the Andes that in turn is due to increased Miocene Pacific Ocean crustal spreading and subduction rates, which peaked at about 10 to 20 Ma (Pardo-Casas and Molnar, 1987;Martinod et al, 2010). However, the routes or processes by which…”
Section: Background and Geological Settingmentioning
confidence: 99%
“…However, a number of papers published since 2009 reported new high-resolution and/or multichannel seismic surveys (Fig. 4), often combined with multi-beam bathymetric data, which show the common occurrence of layered sediments and prominent sediment drifts on the Argentine and adjacent Uruguayan margins (e.g., Hernández-Molina et al, 2009Violante et al, 2010, Krastel et al, 2011Lastras et al, 2011;Muñoz et al, 2012;Grützner et al, 2011Grützner et al, , 2012Grützner et al, , 2016Preu et al, 2012Preu et al, , 2013Voigt et al, 2013;Uenzelmann-Neben et al, 2016; see also Hinz et al, 1999). There has also been significant progress studying the climatic records in surficial and near-surface sediments recovered in sediment cores from the Argentine margin (e.g., Chiessi et al, 2007;Bozzano et al, 2011;Govin et al, 2012;Bender et al, 2013;Razik et al, 2013;Razik, 2014;García Chapori et al, 2014, demonstrating that this margin also contains important modern sedimentary deposits.…”
Section: Background and Geological Settingmentioning
confidence: 99%